Saccharomyces cervisiae ameliorative impact combined with sulfaclozine on broiler chicken oxidative status - Nahla M. Ali; Mohamed K. Hussein; Nady Khairy Elbarbary; Zeinab-El Amgad; Enas A. Noseer (BMC Veterinary Research)
Abstract Poultry production has expanded, and imports from other countries have surged due to the sharp growth in demand for chicken meat. The purpose of this study was to determine the effect of different doses of sulfaclozine 30%, either alone or in conjunction with Saccharomyces cerevisiae (yeast), on body weight gain, biochemical markers, oxidative status, and histopathological variation in broilers’ organs. One hundred fourteen -day-old chicks were divided into five groups for this experiment (20 each). For a total of 20 days, the first group was used as a control; the second group received 30 mg/kg of sulfaclozine; the third group received 70 mg/kg; the fourth group received 1.5 g/L of Saccharomyces cerevisiae followed by 30 mg/kg of sulfaclozine; and the final group received 70 mg/kg of sulfaclozine after taken 1.5 g/L of Saccharomyces cerevisiae. Hepatic and renal functions, along with malonaldehyde levels, were much higher in the chickens that received 70 mg/kg of sulfaclozine followed by 30 mg/kg; however, total protein, albumin, and catalase levels were much lower, and signs of liver and kidney damage were seen. On the other hand, the groups that received sulfaclozine treatments subsequent Saccharomyces cerevisiae showed improved metabolic indices and a partial recovery from the histopathological change.